PEMBERIAN TERAPI NEBULIZER UNTUK MENGATASI KETIDAKEFEKTIFAN BERSIHAN JALAN NAFAS PADA AN.A DENGAN BRONKOPNEUMONIA DI RUANG PARIKESIT RST.WIJAYAKUSUMA PURWOKERTO - Riana Retno Kusmianasari; Rizki Sufiana Arsy; Roro Lintang Suryani (JURNAL PENGABDIAN MANDIRI, 2022)
Background : Bronchopneumonia is a form of inflammation that occurs in the bronchial area and triggers the production of mucopurulent exudate which results in respiratory obstruction resulting in even consolidation of the adjacent lobes. Symptoms that often appear are coughing with phlegm, runny nose and shortness of breath due to excessive sputum production in the respiratory tract, resulting in ineffective airway clearance. One of the independent interventions that can be done is to provide nebulizer therapy, nebulizer therapy is a type of therapy that is given through the airways which aims to overcome disorders or diseases in the lungs, the purpose of nebulizer therapy is to deliver drugs directly to the target organ, namely the lungs. lungs, without having to go through the systemic route first. Objective: To be able to know the administration of nebulizer therapy to overcome the ineffectiveness of airway clearance in child A with bronchopneumonia in the Parikshit Room, RST. Wijayakusuma Purwokerto. Methods: Descriptive observation with a case study approach. The subject in this study was one patient with bronchopneumonia in a child who was treated at the Parikesit Room at RST Wijaya Kusuma Purwokerto, aged 4 years.